Slow gender-transformative change in Nepal’s water sector offers lessons for CGIAR initiatives - Buchy, Marlene (International Livestock Research Institute, 2023)
What can CGIAR’s new initiatives and other research for development projects learn from Nepal’s slow progress toward gender equality, despite its progressive policies? In this blog post, Marlène Buchy, a senior social scientist with International Water Management Institute – Nepal, shares personal reflections on strategies for getting past institutional bottlenecks that stand in the way of true gender-transformative change in food systems.